2021
DOI: 10.3892/mmr.2021.12172
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA TUG1 inhibits the cancer stem cell‑like properties of temozolomide‑resistant glioma cells by interacting with EZH2

Abstract: Temozolomide (TMZ) is currently one of the first-line drugs used for the treatment of high-grade gliomas. However, TMZ resistance results in unsatisfactory therapeutic effects in gliomas. Cancer stem cells (CSCs) have recently been determined to serve a pivotal regulatory role in tumor metastasis, recurrence and chemoresistance. In addition, numerous reports have shown that long non-coding RNAs (lncRNAs) exert an essential role in the occurrence and development of tumors, and can be used as biomarkers for tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 44 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…A172 glioma cells resistant to temozolomide also represent higher CSC-like properties compared to parental cells. The silencing of TUG1 or overexpression of EZH2 enhances CSC-like properties and resistance to temozolomide in A172 glioma cells [192]. EZH2 is a key epigenetic regulator that is suggested to be dysregulated in specific BC types, particularly in advanced stages [193,194].…”
Section: Regulation Of Cancer Stemness By Lncrna In Chemoresistant Bc...mentioning
confidence: 99%
“…A172 glioma cells resistant to temozolomide also represent higher CSC-like properties compared to parental cells. The silencing of TUG1 or overexpression of EZH2 enhances CSC-like properties and resistance to temozolomide in A172 glioma cells [192]. EZH2 is a key epigenetic regulator that is suggested to be dysregulated in specific BC types, particularly in advanced stages [193,194].…”
Section: Regulation Of Cancer Stemness By Lncrna In Chemoresistant Bc...mentioning
confidence: 99%
“…Furthermore, lncRNA CACS2 acts as a ceRNA molecule to reverse the resistance of tumour cells to TMZ, primarily through the miR-193a-5p/mTOR signalling pathway-mediated inhibition of autophagy. The results of in vivo and in vitro experiments indicated that lncRNA taurine upregulated gene 1 inhibits the EMT process and GSC phenotype of gliomas by downregulating the expression of enhancer of zeste homologue 2 (EZH2), thereby reducing TMZ resistance ( 126 ). In addition, lncRNAs have been indicated to affect the apoptosis of TMZ-resistant glioma cells.…”
Section: Lncrnas and Glioma Drug Resistancementioning
confidence: 99%
“… 290 TUG1 EZH2 in vitro , in vivo Cao et al. 291 HOXB-AS1 in vitro Shao et al. 292 H19 in vitro , in vivo , human Jiang et al.…”
Section: Introductionmentioning
confidence: 99%
“… 340 TUG1 lncRNA alleviated TMZ resistance and inhibited tumorigenicity downregulating EZH2 expression Cao et al. 291 SNHG9 lncRNA facilitates growth of GSCs competitive endogenous RNA of miR-326 to elevate the expression of SOX9 Wang et al. 341 RP11-279C4.1 lncRNA functions as an oncogene that promotes tumour progression modulating the miR-1273g-3p/CBX3 axis Wang et al.…”
Section: Introductionmentioning
confidence: 99%